COMPARISON OF BIOMARKERS AS MONITORING TOOLS FOR HEAVY METALS IN KAMPAR RIVER, RIAU PROVINCE, INDONESIA - Yudho Harjoyudanto; Andri Hendrizal; Novreta Ersyi Darfia; Budijono Budijono (Berkala Perikanan Terubuk, 2023)
In Indonesia, the study of biomarkers is still very few because not many biomarkers are understood in various inland public waters here. The research location was at the Koto Panjang Reservoir as the experimental location and the Sei Tiban Fish Seed Center as the control location. The fish tested were carp and tilapia. Sample analysis was carried out in a certified laboratory at Construction Materials Laboratory, Department of Public Works, and Genetics Laboratory, Universitas Riau. The biomarkers studied were LSI, GSI and MT, and heavy metals observed were Cd, Pb and Hg. The research method was Experimental Design. Based on the statistical test, there was no difference in the LSI value of tilapia in the treatment group and tilapia in the control group (p = 0.187; p > 0.05), while it was different from goldfish (p = 0.0000; p < 0.001). In GSI, both of tilapia and carp showed significant differences (p = 0.0010; p < 0.010) and (p = 0.0060; p < 0.010). The tilapia and carp-treated livers showed the presence of MT while not in the control fish. This indicates that MT can be used as a biological marker of heavy metal exposure compared to GSI and LSI.